Evaluation of marine economic development demonstration zone policy on marine industrial structure optimization: a case study of Zhejiang, China - Cui, Yuhu; Xu, Hanxiao; An, Dong; Yang, Lin (Frontiers in Marine Science, 2024)
The marine economic development demonstration zone (MEDDZ) is the regional marine functional policy that assumes the significant tasks of innovation in the system and mechanism of the marine economy, optimization of the marine industrial structures, and the construction of marine ecological civilization. This paper constructs a panel database of 11 coastal provinces in China from 2006 to 2019, takes the Zhejiang Marine Economy Development Demonstration Zone Plan officially approved by the State Council of China in 2011 as a quasi-natural experiment, applies the synthetic control method (SCM) to evaluate the effect of implementation of the MEDDZ policy on marine industrial structure optimization in Zhejiang. The results show that: (1) The MEDDZ policy significantly promotes the structure optimization of the marine industry in Zhejiang and the existence of the policy lag phenomenon. (2) Based on the results of the robustness tests, we find that the fitted path of policy effects is better when the time of MEDDZ implementation is adjusted to 2012. (3) Government financial support and marine cargo capacity play a role in implementing the MEDDZ policy, positively affecting and optimizing the coastal marine industry's structure.Therefore, we make some suggestions from the perspectives of strengthening the policy implementation process, focusing on the policy lag phenomenon, and broadening funding sources, thus enriching theoretical research on policies in the field of the marine industry and providing practical references for the development of other coastal demonstration zones.